Making sense of climate: A meta-analytic extension of the competing values framework. (August 2020) - Beus, Jeremy M.; Solomon, Shelby J.; Taylor, Erik C.; Esken, Candace A.
Organizational climate research has surged recently, but the disbursement of research contributions across domains has made it difficult to draw conclusions about climate and its connections with performance. To make sense of the climate literature, we used the competing values framework (CVF) to classify domain-specific climates into four climate types (clan, adhocracy, hierarchy, and market climates). We did so by conceptually linking domain-specific climates that are manifestations of the same underlying strategic values. We then conducted meta-analyses to examine the magnitudes, mechanisms, and moderators of the individual and group-level associations between the CVF climates and performance. These meta-analyses revealed positive climate–performance associations for each climate type and supported job attitudes as a common mediator. We also examined several methodological moderators of climate–performance relationships, testing the source of climate and performance measures, the temporal assessment of these constructs, and the level of within-group agreement in climate measures as possible boundary conditions.